2014
DOI: 10.1152/jn.00267.2014
|View full text |Cite
|
Sign up to set email alerts
|

Nonmigraine-associated TRESK K+ channel variant C110R does not increase the excitability of trigeminal ganglion neurons

Abstract: Guo Z, Liu P, Ren F, Cao YQ. Nonmigraine-associated TRESK K ϩ channel variant C110R does not increase the excitability of trigeminal ganglion neurons. J Neurophysiol 112: 568 -579, 2014. First published May 7, 2014 doi:10.1152/jn.00267.2014.-Recent genetic studies suggest that dysfunction of ion channels and transporters may contribute to migraine pathophysiology. A migraineassociated frameshift mutation in the TWIK-related spinal cord K ϩ (TRESK) channel results in nonfunctional channels. Moreover, mutant TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 50 publications
(106 reference statements)
4
27
0
Order By: Relevance
“…This mutation segregated perfectly with the MA phenotype in a large pedigree and was shown to produce a non-functional protein that can serve as a dominant negative that functionally downregulates the wildtype (WT) TRESK channel (Lafreniè re et al, 2010;Wood, 2010). TRESK-MT has been shown to induce hyperexcitability of TG neurons (Guo et al, 2014;Liu et al, 2013), which likely underscores its role in migraine. However, in subsequent genetic screening studies, another missense TRESK variant, C110R, was identified (Andres-Enguix et al, 2012).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…This mutation segregated perfectly with the MA phenotype in a large pedigree and was shown to produce a non-functional protein that can serve as a dominant negative that functionally downregulates the wildtype (WT) TRESK channel (Lafreniè re et al, 2010;Wood, 2010). TRESK-MT has been shown to induce hyperexcitability of TG neurons (Guo et al, 2014;Liu et al, 2013), which likely underscores its role in migraine. However, in subsequent genetic screening studies, another missense TRESK variant, C110R, was identified (Andres-Enguix et al, 2012).…”
Section: Introductionmentioning
confidence: 89%
“…Together, these data show that TRESK-MT can inhibit TRESK, TREK1, and TREK2, whereas TRESK-C110R is only able to inhibit TRESK. Based on the fact that TRESK-MT, but not TRESK-C110R, is able to induce TG neuron hyperexcitability (Guo et al, 2014;Liu et al, 2013), we hypothesized that TRESK-MT induces sensory neuron hyperexcitability primarily by acting on TREK1 and TREK2, not TRESK.…”
Section: Tresk-mt But Not Tresk-c110r Acts As a Dominantmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is important to note that other missense mutations in TRESK channels, including one which resulted in complete lack of channel function (C110R), did not show a correlation with the presence of migraine in patients ( [3], see also [40,62]). …”
Section: Tresk Channelsmentioning
confidence: 99%